Converting the British Library's Catalogue of British and Irish Newspapers into a Public Domain Dataset: Processes and Applications. (22nd January 2021) - Ryan, Yann; McKernan, Luke
This paper describes the production of a title-level list of British, Irish, British Overseas Territories and Crown Dependencies newspapers (1621–2019) held by the British Library, and its potential for reuse and research. The data was extracted from the British Library's catalogue of over 24, 000 British and Irish newspaper titles, cleaned, and published on the British Library Research Repository, an open access repository for the research produced by staff and research associates of the British Library. Bespoke versions of the data have been made available to specialist users, notably the British Library/Alan Turing Institute's 'Living with Machines' project, enabling greater historical analysis of nineteenth-century British news and selective digitisation.